Personal values of accountants and accounting trainees in Cyprus - Zopiatis, Anastasios; Krambia-Kapardis, Maria (My University, 2011)
Accountants are neither devoid of ethical dilemmas nor are they immune from financial scandals. In order to improve the credibility of the profession, it is important to study the personal values that qualified and trainee accountants consider important. Using Maccoby's instrument, which measures 'head' and 'heart' values, qualified accountants (chartered and certified) and trainee accountants were surveyed for the first time in a European Union member country (Cyprus) to ascertain their character ethical traits/personal values. Accountants were found to value 'head' more than 'heart' traits and there were no gender differences. For male respondents, age and years of professional experience were significant correlates of the importance attributed to head traits, while having religious beliefs was associated with valuing heart traits more. Finally, the implications for accounting education and the professional bodies are considered.
Keywords: Oppression; Black Person; Feminism